2018
DOI: 10.1126/sciimmunol.aar6689
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D plays a vital role in the generation of neutrophil extracellular traps

Abstract: The death of a cell is an inevitable part of its biology. During homeostasis, most cells die through apoptosis. If homeostasis is disturbed, cell death can switch to proinflammatory forms of death, such as necroptosis, pyroptosis, or NETosis. We demonstrate that the formation of neutrophil extracellular traps (NETs), a special form of neutrophil cell death that releases chromatin structures to the extracellular space, is dependent on gasdermin D (GSDMD). GSDMD is a pore-forming protein and an executor of pyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
566
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 533 publications
(623 citation statements)
references
References 38 publications
15
566
5
3
Order By: Relevance
“…However, whether GSDMD promotes spontaneous neutrophil cell death is controversial, as other studies documented similar rate of spontaneous neutrophil death in wildtype versus Gsdmd-deficient neutrophils (Chen et al, 2018b;Burgener et al, 2019). In agreement with macrophage studies showing that the GSDMD NT fragment triggers proinflammatory cell death, a second study reported that activation of GSDMD by neutrophil elastase drives neutrophil cell lysis and NET extrusion, a well-appreciated antimicrobial defence mechanism (Sollberger et al, 2018). Therefore, it appears that GSDMD activity in neutrophils can either promote or dampen host defence.…”
Section: Neutrophil Elastase Cleaves Gsdmd To Trigger Neutrophil Cellsupporting
confidence: 69%
“…However, whether GSDMD promotes spontaneous neutrophil cell death is controversial, as other studies documented similar rate of spontaneous neutrophil death in wildtype versus Gsdmd-deficient neutrophils (Chen et al, 2018b;Burgener et al, 2019). In agreement with macrophage studies showing that the GSDMD NT fragment triggers proinflammatory cell death, a second study reported that activation of GSDMD by neutrophil elastase drives neutrophil cell lysis and NET extrusion, a well-appreciated antimicrobial defence mechanism (Sollberger et al, 2018). Therefore, it appears that GSDMD activity in neutrophils can either promote or dampen host defence.…”
Section: Neutrophil Elastase Cleaves Gsdmd To Trigger Neutrophil Cellsupporting
confidence: 69%
“…In addition, the secretion of cytokines and mediators through GSDMD pores recruits neutrophils that remove these pore‐induced intracellular traps by efferocytosis, assisting the control of bacterial infection . Furthermore, recent studies linked GSDMD to the release of neutrophil extracellular traps (NETs), a cell death process termed NETosis . These structures are composed of neutrophil DNA and granular proteins such as neutrophil elastase (NE), myeloperoxidase, and cathepsin G. These NETs act as a barrier that avoids bacterial spreading and also kill pathogens by degrading their virulent factors .…”
Section: Gasdermin: the Executor Of Pyroptosismentioning
confidence: 99%
“…These structures are composed of neutrophil DNA and granular proteins such as neutrophil elastase (NE), myeloperoxidase, and cathepsin G. These NETs act as a barrier that avoids bacterial spreading and also kill pathogens by degrading their virulent factors . In view of that, GSDMD can be cleaved by serine proteases such as NE . Once it is cleaved, it leads to pore formation in the membrane of neutrophil azurophilic granules, thus contributing to enhance NE release in the cytosol .…”
Section: Gasdermin: the Executor Of Pyroptosismentioning
confidence: 99%
See 2 more Smart Citations